Peningkatan Pendapatan Pelaku UMKM di Kecamatan Tanjung Pura Kabupaten Langkat melalui Pelatihan Strategi Pemasaran dengan Menggunakan Aplikasi E-Commerce - Agnes Tambunan; Juli Friska; M Dede Yusuf; Nurul Hanani; Riki Thomas; Rosari Serena; Ronaldo Fransiskus; Rizqy W Asmara (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2022)
This community service aims to help Small and Medium Enterprise groups (SMEs), especially SME business actors in Tanjung Pura District, Langkat Regency who experience difficulties in marketing their products. So far, SME actors in Tanjung Pura District, Langkat Regency have used a traditional marketing system where SME actors only rely on customer visits along the Medan-Aceh causeway to buy the typical products offered. In addition to marketing methods that are still traditional, SME business actors are still lacking in terms of information technology literacy, especially literacy in the use of digital media as a marketing alternative which is growing rapidly. In addition to the problems above, SME business actors in Tanjung Pura District are also not optimal in product innovation. Given the problems above, the Community Service Team seeks to help overcome the above problems by providing education and training on the benefits of using e-commerce applications in product marketing and helping create online stores on e-commerce applications, namely Shoppe. Product marketing with e-commerce is expected to help SME actors optimize the development of digital media to increase their product sales.